Nivel de aplicación de la Tributación Ambiental y sus efectos en la Gestión y Desarrollo Socioeconómico de las sociedades anónimas cerradas de la ciudad de Tarapoto - Vásquez Yalta, Jhoysy Sarita (2012)
In recent years there has been presenting a special sensitivity on the issue of care for the natural, known to us as protecting the environment, all this due to problems with waste produced by companies in their production process and commercial, as well as mismanagement given to natural resources by all those who need these resources to satisfy their needs, which has caused great natural and serious danger to the same population. For this reason it has been decided to carry out this work to determine the current situation reflects the companies in the application and knowledge of this very important and relevant in our globalized world, which is generated specifically for each person and as a result of acts independently of their work to engaged. Although from a macroeconomic point of view is a widely discussed at the micro level has not been sufficiently treated, especially in our country, with a theme and an important area to consider and study a certain way can help though either with the minimum and improve where we live, and especially that the initiative is born from the internal environment of each company, and what better to start with the companies in our city of Tarapoto. The following research work aims at illustrating the statistics and attainment of knowledge and application of internal policies and how sorne situations are considered binding on this issue, and shows the degree of implementation would be willing to use in relation to internal policies the influence that leads to action with another, as well as situations in which they might be partakers of public bodies. With the completion of this research work will have a clear and deep knowledge about the real situation reflected in this case held corporations in the city of Tarapoto, since it is a consolidation of real data applied in the daily actions of their production which is involved from top management down to the last worker may have. With the information obtained may be the basis for a larger study on this important issue and concern, that involves us ali its inhabitants, so that in one way or another is necessary forms and ideas to improve and provide in the care and maintenance of a protected environment and sustainable development and I or sustainable.